Experimental Investigation and Simulation of Electro-Mechanical Behaviour of Hybrid Sandwich Composite Radomes for Aerospace Applications - Zhaib Muneer Ahmed; Muhammad Ali Nasir; Zafar Iqbal; Muhammad Talha Aamir (Mechanics of Advanced Composite Structures)
This paper presents a comprehensive study of the material selection, manufacturing, and Electro-Mechanical testing of radomes made from Polymer Matrix Sandwich Composite materials. The objective is to achieve optimal electromagnetic (EM) and mechanical performance using a combination of PMI foam core and hybrid face sheets (Kevlar & S Glass) sandwich composite structures. The selection of the material configuration was based on a Multi Criteria Decision Matrix (MCDM) method to meet the requirements of Electromagnetic Interference (EMI) transparency and aerodynamic/inertial loads during flights. A full-scale nose radome was manufactured using a hand-layup technique assisted by vacuum bagging, specifically designed for flight vehicles with speeds up to <0.8 Mach. The EMI behavior of the radome was experimentally tested using the free space measurement method and verified through numerical modeling in Altair FEKO software, which showed minimal EM losses of 3% and <1% respectively. Multiple specimens were prepared to determine the mechanical properties and were tested according to ASTM standards for tensile and flexural properties. Additionally, finite element modeling (FE) was employed to validate the mechanical properties of the radome, ensuring that it meets the required constraints. The combined results from the EMI testing, FE modeling, and mechanical testing provided an optimum combination of materials and structure that satisfies the functional requirements of the radome.